The Association between Depression and Anxiety Symptoms with Six Core Components of Social Networking Sites Addiction – a Cross-sectional Study in Serbia: Depression and Anxiety with Social Networking Addiction - Jovanović, Tamara; Aleksandar,; Gmijović, Marko (Acta medicae Medianae, 2020)
Background and Objectives: It would seem that today, for many individuals the most important thing is to have a good profile picture on online social networks. Accordingly, there is a serious possibility that addiction to social networking sites (SNS) can lead to psychosocial and behavioral disorders, and other negative consequences on health-related issues. So, the aim of this study was to determine the association between the excessive use of social networking sites with the symptoms of depression and anxiety.Methods: This cross-sectional study was carried out at the University of Niš, Faculty of Medicine (Serbia) from September to December, 2019. The study included 1,405 participants and all of them were assessed by using an appropriate questionnaire. The statistical analysis of the data included the binary logistic regression.Results: The strongest predictor of whether one has high levels of depression symptoms was state of conflict, where the odds ratio (OR) was 10.28 (95% CI: 5.84–18.08). It has been observed that depression symptoms are also more common in those respondents with expressed withdrawal symptoms (OR=4.27, 95% CI: 3.04–6.00), and with mood modification (OR=1.82, 95% CI: 1.12–2.96). Anxiety symptoms, similar to those of depression, are most present in individuals with conflict state (OR=10.31, 95% CI: 5.25–20.26), in those with withdrawal symptoms (OR=6.83, 95% CI: 4.98–9.38), and then with mood modification (OR=2.55, 95% CI: 1.60–4.07). The number of active accounts/profiles and number of devices, as well as state of salience and tolerance played no part in any of the cases.Conclusion: This study has shown a direct link between excessive SNS use and depression and anxiety symptoms. Further detailed research, especially longitudinal studies, is needed to understand the essential nature of these links. In any case, public health professionals should draw the attention of people, especially the younger population, in terms of limiting the use of social networks.
Keywords: online social networking; addiction; depression; anxiety